Perceptions of Bahir Dar University teacher educators about functions of education in Ethiopia - Mulugeta Yayeh Worku (College of education, Bahir Dar University, 2023)
Using the four major philosophies of education (Perennialism, Essentialism, Progressivism, and Social Reconstructionism) as its theoretical framework, this study examined the perceptions of teacher educators about the functions of education in Ethiopia. The study adopted the qualitative research approach and employed the case study as a design. Through a purposeful criterion-based sampling technique, six teacher educators from Bahir Dar University were selected as participants in the study. Data pertinent to the study were collected through semi-structured interviews and document reviews. The data collected through these methods were thematically analyzed. The results of the study revealed the existence of multifarious perceptions among teacher educators. To be specific, the teacher educators were found to be proponents of the perennialist, essentialist, and progressivist educational purposes. As far as the function of education in Ethiopia was concerned, the study revealed that the perennialist and essentialist purposes of education were dominant. Educational purposes advocated by the progressive educational philosophy were also found to be important. The social reconstructionist function of education, however, was not given an adequate place. Finally, the implications of these findings for the country's teacher education programs and policymaking initiatives are indicated.